The influence of social support on sleep and fatigue level among patients receiving hemodialysis in Saudi Arabia: a cross-sectional correlational design - Alshammari, Bushra; Alkubati, Sameer A.; Pasay-an, Eddieson; Alrasheeday, Awatif; Madkhali, Norah; Edison, J. Silvia; Bakthavatchaalam, Venkat; Alshammari, Marim Saud; AlRashidi, Amnah Ayed; Alshammari, Farhan (Frontiers in Psychology, 2023)
Background:Patients on hemodialysis (HD) are more likely to experience sleep problems and fatigue that may affect their health outcomes. Management of these patients with social support may improve their sleep quality and fatigue as well as their health. Aim: This study aimed to assess the influence of social support on sleep quality and fatigue levels among HD patients. A cross-correlational study was conducted among 260 conveniently sampled HD patients from four dialysis centers in Saudi Arabia from Jun 2022 to January 2023. the study utilized three instruments: the Pittsburgh Sleep Quality Index (PSQI), the Multidimensional Assessment of Fatigue (MAF) and the Oslo Social Support Scale (OSSS-3) to assess sleep, fatigue levels and social support, respectively. Poor sleep and high fatigue were significantly higher in older patients compared to younger patients (p ˂0.001), while strong social support was significantly lower in older patients than younger and middle-aged ones (p = 0.001). Poor sleep and high fatigue were significantly higher in males than females (p = 0.022 and p ˂0.001, respectively), while strong social support was significantly higher in females than males (p ˂0.001). Married patients showed significantly poorer sleep than single ones (p = 0.019), but single patients received significantly stronger social support. Retired patients showed significantly poorer sleep, higher fatigue and weaker social support than other groups (p˂0.001). There was a significant negative correlation between fatigue and sleep quality among HD patients, where patients with more fatigue had poorer sleep (r = -0.510, p ˂0.001).A significant positive correlation was found between social support and sleep quality, where patients with stronger social support had more normal sleep (r = 0.415, p ˂0.001). However, a significant negative correlation was found between social support and fatigue, where patients with stronger social support had lower levels of fatigue (r = -0.479, p ˂0.001).Saudi patients on HD who have stronger social support have better sleep quality and reduced fatigue levels than those with less social support. There is a need to design and implement intervention studies with structured social support programs, and to evaluate their effectiveness on improving sleep and reducing fatigue among HD patients.